Reformar el art. 69 del Código De Trabajo, sobre el derecho a gozar anualmente de vacaciones para el trabajador en general, que será de treinta días - Paladines Costa, María Belén (2015)
Since mankind was organized as society began to feel the need to regulate the rights, duties and obligations of all individuals that formed, but all involved as a global entity. Where all individuals should be considered on equal rights and opportunities in everyday scope of their activities, which could never prevail the benefits of a social sector on the other. One of the most important legal, social and economic proposals was to regulate labor relations established between employer and employee, ie legally regulate the operation of production systems. Within the workplace, concomitant with the obligations of field workers, the enjoyment of their rights and within the right of all workers to enjoy a fixed period and determined rental is also strengthened. Since it is shown that the human being comes to a higher production rate in the labor chain when it respects and encourages their abilities and attitudes, and also allows the recovery of their physical and mental strength product a rest . Thus, in 1948 when the Universal Declaration of Human Rights is made in the United Nations General Assembly, in its Article 1, the following is determined.: "All human beings are born free and equal in dignity and rights are endowed with reason and conscience and should act towards one another." . And also, in its Article 23 provides: "Everyone has the right to rest and leisure, including reasonable limitation of working hours and periodic holidays with pay." The Ecuadorian legislators aware that all individuals who live in this beautiful country should have the same rights and obligations, has seen fit to explicitly regulate the Constitution of the Republic of Ecuador as previously stated. Thus, its Art 11 addresses. "EI exercise of rights shall be governed by the following principles:" in its paragraph 2 provides: "All people are equal and enjoy the same rights, duties and opportunities." The art. 66, paragraph 2, of the Constitution of the Republic of Ecuador, provides: 2. "The right to a dignified life, ensuring health, food and nutrition, clean water, shelter, sanitation, education, labor, employment, rest and leisure, physical culture, dress, social security and other social facilities. " And equally, Ecuadorian legislators in order that the rights of workers in relation to their annual leave are not trampled and unknown, specifically provided for in the Labour Code in its Art.69 the following: "Holidays anuales.- Every worker is entitled annually to enjoy an uninterrupted period of fifteen days of rest, including non-working days. Workers who have served for more than five years in the same company or the same employer are entitled to additionally enjoy a vacation day for each year of surplus cash or receive the full amount of the surplus days pay. " . But unfortunately, in a clear attitude of inequality and inequity frank position, contrary to the workers covered and subject to the rules of the Labour Code, the Organic Law of Public Service LOSEP, in its Article 29 provides: "All Holidays and permisos.- servant or public servant will be entitled to thirty days of paid annual leave after eleven months of continuous service. This right may not be compensated in cash, except in the case of cessation of functions that unused vacation according to perceived value or had received for his last vacation was settled. The leave may be accumulated up to sixty days. " For the foregoing transcript, I believe, never legal norms can have an inequity in the enjoyment of the rights and legal provisions in the workplace, must go hand in hand with the provisions of the Universal Declaration of Human Rights and also with the rule our Constitution, but considering all workers equal. Moreover, as a student of the race of Law Distance Learning mode, you must always be aware and be observant of legal, social and labor reality that exists today, to legally analyze the problems that arise in the same and try to find a solution, from the perspective of law enforcement and search and improvement of the laws that govern us. Under the statement, consider that Article 69 must reform the current Labour Code of the Republic of Ecuador, so this problem neatly proposal should be studied and that tends to give an alternative solution to the issues raised. As indicated above and under what determines the object of transformation for this Module, has seen fit and compulsory noted as a research subject, a subject line with our social, legal and labor reality